LANGUAGE STYLES OF THE MAIN CHARACTER IN FLIPPED MOVIE: A SOCIOLINGUISTIC STUDY - Fadya Lisarah; Malikatul Laila (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2026)
This study aims to identify and classify the language styles of the main character in the film Flipped (2010) and to determine the dominant style using Martin Joos’ (1967) language style theory. The study employs a qualitative, descriptive method. The data comprise 17 utterances made by the main character, collected through repeated observation, transcription, and coding. The analysis follows Joos’ five style categories: frozen, formal, consultative, casual, and intimate. The results show that the main character uses three of the five language styles: the intimate style (7 utterances, 41.2%), the casual style (6 utterances, 35.3%), and the consultative style (4 utterances, 23.5%). No examples of frozen or formal language styles were found; the predominant language style is intimate style, characterized by elliptical structure, high emotional intensity, and the assumption of shared knowledge. This dominance reflects the emotional depth, psychological reflection, and involvement of the main character in intimate personal relationships-elements appropriate for the demanding film genre. The study confirms that the social context, the status of the interlocutor, and the communicative intention suggest a systematic relationship. It contributes to this analysis by applying Joos’s model, which focuses on individual characters within cinematic discourse.